Lighthouse Modernization through Unmanned Systems: Advancing Maritime Navigational Safety - Kamia, Shaffiyah Cantika; Hadiningrat, K.P. Suharyono S.; Silalahi, Verry Albert Jekson Mardame (JIPOWER : Journal of Intellectual Power, 2025)
Lighthouses are crucial part of Aids to Navigation, playing a vital role in ensuring maritime safety in Indonesian waters. Currently, lighthouse operations still rely on human resources, Lighthouse Keepers and Technicians, who are stationed in outposts and face various operational challenges. This condition necessitates the modernization of lighthouse management systems to enhance efficiency and adaptability in maritime safety challenges. This study explores the concept of an unmanned system as an optimal solution for lighthouse operations by leveraging technologies such as satellite-based monitoring applications, drones, and hazard detection radar. Through the implementation of this system, lighthouses can be managed remotely without the need for continuous on-site personnel presence. The proposed operational model not only improves the efficiency of lighthouse monitoring and maintenance but also minimizes safety risks for field personnel. This idea was first introduced by Hendaviny Kartomo, SE, M.Kom, a famous marine transportation professional who is the Head of Distrik Navigasi Tipe A Kelas II Banjarmasin. The notion has been presented at several internal maritime transportation forum. With this modernization, it is expected that maritime navigation safety and efficiency in Indonesia will be significantly enhanced.